2021
DOI: 10.1093/ons/opaa413
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Transposition Without Teflon: A Single Institution's 17-Year Experience Treating Trigeminal Neuralgia

Abstract: BACKGROUND Trigeminal neuralgia (TN) refractory to medical management is often treated with microvascular decompression (MVD) involving the intracranial placement of Teflon. The placement of Teflon is an effective treatment, but does apply distributed pressure to the nerve and has been associated with pain recurrence. OBJECTIVE To report the rate of postoperative pain recurrence in TN patients who underwent MVD surgery using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Recently, several studies have suggested that the offending vessel should be removed reliably and thoroughly from the neurovascular compression site rather than inserting a decompression material between the culprit vessel and trigeminal nerve ( Fig. 2 ) [ 12 , 35 , 37 , 48 , 67 ]. This method, first proposed by Fukushima [ 22 ], completely separates the trigeminal nerve and the offending vessel.…”
Section: Decompression Techniquementioning
confidence: 99%
“…Recently, several studies have suggested that the offending vessel should be removed reliably and thoroughly from the neurovascular compression site rather than inserting a decompression material between the culprit vessel and trigeminal nerve ( Fig. 2 ) [ 12 , 35 , 37 , 48 , 67 ]. This method, first proposed by Fukushima [ 22 ], completely separates the trigeminal nerve and the offending vessel.…”
Section: Decompression Techniquementioning
confidence: 99%
“…Indeed, a tentorial sling technique was proposed a few years ago, which aimed to generate offending vessel transposition without the use of foreign materials 7 . Other techniques have also been used, including using biological glue 8 or a vascular clip 9 . Moreover, several doctors claim that the cranial nerve V could be split into 6 to 8 bundles longitudinally by its fibers, which requires lower rates of pain relief, and recurrence are lower than CMVD technique.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, we prefer to perform a "Teflon-free MVD" using fibrin glue to attach the superior cerebellar artery to the tentorium, as well as a fenestrated clip and/or sling in selected cases. 12,13 This technique does require additional distal dissection of the superior cerebellar artery to allow for atraumatic mobilization of the artery to the tentorial surface. Our team has observed that 89.3% of patients who have undergone transposition of the superior cerebellar artery with fibrin glue remain pain free at 3 to 17 years of follow-up.…”
mentioning
confidence: 99%
“…Our team has observed that 89.3% of patients who have undergone transposition of the superior cerebellar artery with fibrin glue remain pain free at 3 to 17 years of follow-up. 13 This technique also eliminates Teflon-associated granuloma formation and gliosis. 14 During microvascular decompression of the trigeminal nerve, it can be more difficult to mobilize a vein than an artery based on their anatomy.…”
mentioning
confidence: 99%
See 1 more Smart Citation